PERAN MADRASAH IBTIDAIYAH DALAM MENUMBUHKAN JIWA WIRAUSAHA ANAK DI ERA DIGITAL - Muhamad Chaerul Sukardi; Iya Najiatul Kamila; Nazwa Khoirotunnisa; Nisa Mudrika; Idham Kholid (STKIP Subang, 2025)
This study discusses the role of Madrasah Ibtidaiyah (MI) in fostering children's entrepreneurial spirit in the digital era characterized by technological developments, social change, and the demands of 21st-century competencies. The main issue raised is the still limited implementation of entrepreneurship education at the MI level, both in terms of curriculum, teacher competency, and the use of learning technology. The purpose of this study is to systematically analyze the role, strategies, obstacles, and opportunities of madrasahs in realizing Islamic-based entrepreneurial values ​​​​amidst the digital transformation. The method used is a Systematic Literature Review (SLR) by analyzing scientific articles, proceedings, and research reports from 2015–2025 that are relevant to the theme of entrepreneurship and Islamic basic education. The results show that MI plays an important role in shaping children's entrepreneurial character through project-based learning, simple entrepreneurial practice activities, and the integration of Islamic values ​​​​in the learning process. The main obstacles include limited curriculum and facilities, while significant opportunities arise through the use of digital technology as an innovative learning tool. The conclusion of this study confirms that MI can be an important foundation in developing children's entrepreneurial spirit that is religious, creative, and adaptive to changing times. The implication is that it is necessary to strengthen digital-based curricula, improve teacher competency, and foster synergy between madrasas, parents, and the community to create a sustainable and Islamic-based entrepreneurial education ecosystem.